Fermentation Characteristics, Tannin Contents and In vitro Ruminal Degradation of Green Tea and Black Tea By-products Ensiled at Different Temperatures - Kondo, Makoto (Asian-Australasian Association of Animal Production Societies (AAAP) and Korean Society of Animal Science and Technology (KSAST), 2014)
Green and black tea by-products, obtained from ready-made tea industry, were ensiled at 10°C, 20°C, and 30°C. Green tea by-product silage (GTS) and black tea by-product silage (BTS) were opened at 5, 10, 45 days after ensiling. Fermentation characteristics and nutrient composition, including tannins, were monitored and the silages on day 45 were subjected to in vitro ruminal fermentation to assess anti-nutritive effects of tannins using polyethylene glycol (PEG) as a tannin-binding agent. Results showed that the GTS and BTS silages were stable and fermented slightly when ensiled at 10°C. The GTS stored at 20°C and 30°C showed rapid pH decline and high acetic acid concentration. The BTS was fermented gradually with moderate change of pH and acid concentration. Acetic acid was the main acid product of fermentation in both GTS and BTS. The contents of total extractable phenolics and total extractable tannins in both silages were unaffected by storage temperatures, but condensed tannins in GTS were less when stored at high temperature. The GTS showed no PEG response on in vitro gas production, and revealed only a small increase by PEG on NH(3)-N concentration. Storage temperature of GTS did not affect the extent of PEG response to both gas production and NH(3)-N concentration. On the other hand, addition of PEG on BTS markedly increased both the gas production and NH(3)-N concentration at any ensiled temperature. It can be concluded that tannins in both GTS and BTS suppressed rumen fermentation, and tannins in GTS did more weakly than that in BTS. Ensiling temperature for both tea by-products did not affect the tannin’s activity in the rumen.